Acanthamoeba keratitis: prevalence, diagnosis, treatment and future trends: a systematic review - Priya, Priyanshi; Yadav, Niraj Kumar; Mishra, Nibha; Kaur, Apjit (International Journal of Research in Medical Sciences, 2025)
Acanthamoeba keratitis (AK) is a rare but severe corneal infection caused by free-living Acanthamoeba species. It is increasingly recognised as a significant cause of visual morbidity, especially among contact lens users. This systematic review follows preferred reporting items for systematic reviews and meta-analyses (PRISMA) 2020 guidelines and analyses studies published between January 2000 and January 2025, focusing on AK prevalence, diagnostics, treatment, and innovations. Our search across databases, including PubMed and Scopus, identified 20 peer-reviewed studies. Findings reveal a 35-50% increase in global AK incidence since 2000, particularly affecting Europe, East Asia, and North America, with 85-90% of cases linked to contact lens wear and the T4 genotype being the predominant strain. Advancements in diagnostics, such as polymerase chain reaction (PCR) testing (with over 95% sensitivity) and in vivo confocal microscopy (IVCM) (with 85-90% sensitivity), have improved early detection. Emerging technologies, including metagenomics sequencing and artificial intelligence (AI)-driven imaging, have further enhanced diagnostic accuracy, achieving a specificity of over 93%. Current treatments rely on a combination of biguanides and diamidines, but prolonged therapies often lead to recurrence, with 20-25% of severe cases requiring keratoplasty. Innovations such as nanocarrier drug delivery, photodynamic therapy (PDT), and genotype-specific antimicrobials are promising. While advancements in the diagnosis and treatment of AK have improved, challenges in reducing the disease burden and improving long-term outcomes remain. The future of AK management hinges on integrating molecular diagnostics and AI into clinical practice, supported by public education on safe contact lens hygiene practices.